影像学逆转的孤立症状性基底动脉狭窄1例A Case of Isolated Symptomatic Basilar Artery Stenosis with Imaging Reversal - 逯青丽，孙超，宋沉生，刘国正，刘佩，刘燕，常乔乔，蔺雪梅，吴松笛(LU Qingli, SUN Chao, SONG Chensheng, LIU Guozheng, LIU Pei, LIU Yan, CHANG Qiaoqiao, LIN Xuemei, WU Songdi ) (Zhongguo cuzhong zazhi, 2025)
孤立症状性基底动脉狭窄（isolated symptomatic basilar artery stenosis，ISBAS）的相关研究较少，治疗方案尚不明确。本文报道1例ISBAS患者经积极药物治疗6个月后，影像学最终发生逆转的诊疗经过。该患者发病时为轻度神经功能缺损，入院后病情迅速恶化，影像学检查显示基底动脉次全闭塞。患者拒绝血管内治疗，予以双联抗血小板药物治疗及高强度他汀类药物治疗6个月。治疗3个月和6个月随访的MRA检查显示，患者基底动脉狭窄逐渐改善，最终逆转。Abstract: There is limited research on isolated symptomatic basilar artery stenosis (ISBAS), and the treatment strategies remain unclear. This article reported the process of diagnosis and treatment of an ISBAS patient whose imaging findings ultimately reversed after six months of aggressive medical therapy. The patient presented with mild neurological deficits at the onset of the disease, but the condition rapidly deteriorated after admission. Vascular examination revealed subtotal occlusion of the basilar artery. The patient refused endovascular treatment and was given dual antiplatelet therapy and high-intensity statin therapy for six months. Follow-up MRA examinations at 3 and 6 months showed progressive improvement in basilar artery stenosis, ultimately leading to its reversal.